Effectiveness of Simulated Prehospital Care Thought Self-Efficacy of Community in Giving First Aid on Traffic Accidents Victim - Rahmania Ambarika (Jurnal Keperawatan, 2017)
EFEKTIFITAS SIMULASI PREHOSPITAL CARE TERHADAP SELFEFFICACY MASYARAKAT AWAM DALAM MEMBERIKAN PERTOLONGAN PERTAMA KORBAN KECELAKAAN LALU LINTAS